Experience of nurses in identifying delirium among cancer patients: A qualitative study - Nurul Huda; Hellena Deli; Sri Wahyuni; Erwin; Satriya Pranata; Sri Wahyuni (Bangabandhu Sheikh Mujib Medical University Journal)
Background: Information about how nurses screen for delirium in cancer patients can provide insights into improving recognition. This study aimed to investigate the experiences of nurses while identifying delirium in cancer patients.